Islamic State's interpretation of Islam and Islamic law concerning women's rights - Pucelj, Maja (Teorija in praksa, 2017)
The paper presents a study on women's rights in the self-declared Islamic State through an analysis of the content of the pamphlet entitled "Women in the Islamic State", which is the first written document that provides detailed insight into this radical Sunni Islamist militant group's conception of women. The study points out the basic ambivalence of the pamphlet, which is expressed as the contrast between the declared and the actual role of women in Islamic State, as well as the contradiction between the desired domestic role of women and encouragement for participation in armed conflicts. The pamphlet uses reductionist and traditional interpretations of citations from the Qur'an.
Keywords: Analiza vsebine; Content analysis (Communication); človekove pravice; družbena vloga; human rights; Islam; Islamska država; Manifesti; Manifestoes; Pravice žensk; sociologija religije; Suniti; woman; Women's rights; ženske